Edukasi Kesehatan Mental pada Santri di Pondok Pesantren Darusy Syahadah Boyolali - Hodiri Adi Putra; Norra Hendarni Wijaya (Yayasan Literasi Sains Indonesia, 2026)
Mental health can be defined as a condition that causes thoughts, behavior, emotions and social relationships to become disturbed. Mental health education is an effective strategy to increase student literacy and awareness about the importance of maintaining mental health. Health education activities can help students recognize symptoms of mental disorders early, reduce stigma, and encourage seeking professional help. Wrong or inappropriate handling will have unpleasant consequences and can even be bad for the students' health. The aim of this community service activity is to increase the knowledge and understanding of students and also to make them more aware of the importance of maintaining mental health and managing emotions well. The method of this activity is carried out by providing health education to students about mental health offline in the hall, using instruments in the form of questionnaires for pre-test and post-test of students' knowledge about mental health, and question and answer discussions followed by consultations regarding mental health including problems felt by the students. The results of the activity showed that there was an increase in students' knowledge and understanding of mental health from before being given education to after being exposed to the material. The suggestion is that further activities need to be provided to be able to provide full awareness and habits in maintaining mental health for students so they can continue to control and manage emotions.